THE IMPACT OF CAREER SYSTEMS, MOTIVATION AND WORK DISCIPLINE ON THE LECTURER PERFORMANCE THROUGH JOB-INSECURITY - Retna Anggitaningsih (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2022)
This study analyzes the effect of career system, motivation, and work discipline on the performance of foundation lecturers at private universities in Besuki Raya Region through job-insecurity. Observations were made at five large private universities in Besuki Raya Region by involving 200 lecturers. The analytical method used is the structural equation model (SEM). The findings and results of the study indicate that: (1) a good career system has a significant positive effect on the performance of private university’s foundation lecturers; (2) motivation to become a more qualified lecturer has a significant positive effect on the performance of private university’s foundation lecturers; (3) work discipline has no significant effect on the performance of private university’s foundation lecturers; (4) the career system has a significant negative effect on job-insecurity; (5) motivation has a significant negative effect on job-insecurity; (6) work discipline has no significant effect on job-insecurity; and (7) job-insecurity has a significant negative effect on the performance of private university’s foundation lecturers in Besuki Raya Region.